2016
DOI: 10.1002/cctc.201501306
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferases: Green Catalysts for Friedel–Crafts Alkylations

Abstract: A set of S‐adenosyl‐l‐methionine (SAM) dependent methyltransferases has been characterized as versatile catalysts for the enzymatic Friedel–Crafts (alkylation) reaction. Although the substrate specificity of the enzymes range from high (in the case of SfmM2, SacF, and ORF19) to moderate (in the case of NovO and CouO), the cofactor spectrum is broad. Modified cofactors decorated with alkyl groups other than methyl were used for biocatalytic Friedel–Crafts alkylation, and conversions up to 99 % were achieved. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In contrast, nature routinely employs S ‐adenosyl‐ l ‐methionine (SAM)‐dependent methyltransferases (MTs) to methylate at O‐, N‐, S‐ and C‐sites. Thus, MTs hold considerable potential for the development of a biocatalytic alkylation platform for small molecules …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, nature routinely employs S ‐adenosyl‐ l ‐methionine (SAM)‐dependent methyltransferases (MTs) to methylate at O‐, N‐, S‐ and C‐sites. Thus, MTs hold considerable potential for the development of a biocatalytic alkylation platform for small molecules …”
Section: Methodsmentioning
confidence: 99%
“…We and others have shown that regiospecific methylation of the 8‐position of 1 b is catalysed by a novel His‐Arg motif, which facilitates the deprotonation of the phenolic proton in the 7‐position, followed by methylation at position 8 by SAM to form 2 b . NovO is also effective in catalysing Friedel–Crafts alkylations by using non‐natural SAM analogues to alkylate 1 b – d regiospecifically . Furthermore, NovO accepts non‐natural substrates such as 3 to form exclusively 4 (Scheme B), which is currently only accessible by this process …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Ther epertoire of C-methylation extends to small molecules,which opens up opportunities to tailor these enzymes as ag eneral platform for biocatalytic C À Cb ond formation (Figure 1a). [20,21] One limitation of this process is the need to prepare these cofactors by chemical synthesis,w hich is laborious,l ow yielding,a nd produces both epimers at the sulfur center. [18][19][20] Ahallmark of NovO is its substrate promiscuity (e.g., 1)and the ability to utilize S-alkylated analogues of SAM to form products such as 2 ( Figure 1a).…”
mentioning
confidence: 99%
“…[18][19][20] Ahallmark of NovO is its substrate promiscuity (e.g., 1)and the ability to utilize S-alkylated analogues of SAM to form products such as 2 ( Figure 1a). [20,21] One limitation of this process is the need to prepare these cofactors by chemical synthesis,w hich is laborious,l ow yielding,a nd produces both epimers at the sulfur center. [22][23][24][25][26] Furthermore,S AM analogues are inherently unstable in buffered solution (t 1/2 942 min for SAM at pH 8).…”
mentioning
confidence: 99%